CONCEPT OF COLOR BUSINESS ANALYTICS IN MODERN MANAGEMENT (Development Service Industry Management, 2023)
In today's business environment, where date is becoming the new gold standard for management decisions, color plays an important role in determining strategies and analyzing market trends. The concept of color business analytics is born at the intersection of marketing, psychology and technology, creating new opportunities for effective management.Color is reflected in all aspects of our lives: it affects our mood, perceptions of brands, even consumer preferences. In modern management, color becomes a powerful tool for analyzing data and making strategic decisions. Color business analytics uses methods and tools to study the impact of colors on consumers, their preferences and reactions, enabling businesses to better understand their customers and optimize product strategies.This article systematizes existing knowledge and tools of business analysis based on various color theories. The aim of the study was to search for empirical evidence to propose color business symbolism as a suitable analytical toolkit in the fields of strategic management and marketing, alongside various financial and economic instruments. The object of the research is modern management and its key concepts. The subject of the study is business analysis tools based on color theory. Various marketing, analytical, and statistical tools were applied during the research, along with general scientific methods such as study, synthesis, and systematization of existing literature sources. One of the key stages involved studying companies operating in Ukraine, diverse in scale and economic sphere. Using modern statistical models, several companies were randomly selected from the sample and analyzed in detail. Based on the analysis and evaluation of specific business representatives in Ukraine, conclusions were drawn regarding the objective necessity of integrating color business analysis terminology into the methodologies of modern managers. Additionally, two areas of their most relevant application were identified.
Keywords: business analytics; management; color theory; enterprises